Peluang Perempuan Menjadi Wali Nikah Di Indonesia - Abdul Aziz; Ghufron Maksum (Al Ashriyyah, 2019)
This article tries to explain the answers to Islamic law related to the system of marriage guardians, especially female marriage guardians in the Muslim world. The majority of the Muslim world who follow the Maliki, Shafi'i and Hambali schools of thought assume that a marriage guardian must be from a man's side so that a marriage is not valid if it is carried out in the absence or without the presence of a male guardian. While there are also scholars who also think that men do not have to be a prerequisite and the legal harmony of a marriage, it means that a woman who is competent as a man can also be the validity of a marriage. This article also explains the meeting point of answers that the Indonesian people already have a reference to the formulation of their own marriage system, namely the Islamic Law Compilation and Presidential Instruction.